Attitude towards violence against women in the relationship and the family social climate in adolescents - María de Jesús Pacheco Vela (Interacciones)
Objective: To determine the correlation between attitudes toward violence against women in the couple relationship and the Family Environment Scale in its dimensions "relation", "stability" and "development" in adolescents of 4th grade to “El Bosque” high school. Method: Not experimental transactional and correlational. 63 students of 4th year high school of which 28 were male (44.4%) and 35 were women (55.6%) was evaluated through the Scale of Attitudes towards violence against women in the couple relationship (Scale VM), and the Family Environment Scale of Moos (FES). Results: Results: There is not correlation between attitudes towards violence against women in the relationship and dimensions of Family Enviroment Scale: Relations (r = - .133, p> .05), Development (r = - .006, p > .05) and stability (r = .112, p> .05). Conclusion: This research is important in the study of attitudes towards gender violence in our environment and its interaction with other factors like the family atmosphere above, which allows a broader vision of this important social issue and encourages broad intervention based on solid knowledge, bringing positive impact on improving the quality of life of people.